2020
DOI: 10.5539/jel.v9n1p156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metacognitive Awareness of Primary and Secondary School Students in Terms of Some Variables

Abstract: Metacognition is important for learners of all ages. Therefore, this situation raises all important questions about how to develop metacognitive skills and habits in the classroom regardless of primary, secondary and high school. The aim of this study is to investigate the metacognitive awareness of primary and secondary school students according to the variables of gender, grade level and region. The model of this research, which was conducted to determine the metacognitive awareness levels of the students in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…Planning activities involve predicting the results, planning strategies or choosing alternative ways while the aspect of monitoring involves testing, rescheduling or revising learning strategies. Although Bakkaloglu (2020) asserted that the literature displays that there are diverse aspects of metacognition, it can be said, according to Alzahrani (2017, p. 525), that "metacognition mainly relates to one's knowledge, monitoring and control of one's own systematic cognitive process, which requires specific skills including planning and evaluation. "…”
Section: Metacognitionmentioning
confidence: 99%
“…Planning activities involve predicting the results, planning strategies or choosing alternative ways while the aspect of monitoring involves testing, rescheduling or revising learning strategies. Although Bakkaloglu (2020) asserted that the literature displays that there are diverse aspects of metacognition, it can be said, according to Alzahrani (2017, p. 525), that "metacognition mainly relates to one's knowledge, monitoring and control of one's own systematic cognitive process, which requires specific skills including planning and evaluation. "…”
Section: Metacognitionmentioning
confidence: 99%
“…POEP learning could mutually reinforce the empowerment of students' metacognition and cognition in learning, especially in science learning. Metacognition awareness is substantial for students in science learning [29], and a conceptual understanding of science is essential as a provision for life [30].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently shown surprising results in students' reading difficulties. Some of these studies have reported issues regarding reading difficulties encountered by students worldwide, such as poor comprehension, lack of world knowledge, and less use of metacognitive skills (Bakkaloglu, 2020;Zarei, 2018). Elgendi et al (2021) reveal that students' reading difficulties may constrain students to experience problems associated with psychological functions, including reading anxiety, procrastination, and self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Higher self-efficacy levels have significant impacts on performance and strategies that are executed by students in academic reading (Aisyi et al, 2021). In developing a higher level of selfefficacy, a higher level of metacognitive awareness is important for students to build the quality of learning nature (Bakkaloglu, 2020).…”
Section: Introductionmentioning
confidence: 99%